Failure of a 2- and 3-Inch Diameter Pipeline of a Steam Generator System-A Case Study - Nazim Mohamed; Frank Byron; Clement Alexander Imbert (Current Approaches in Science and Technology Research Vol. 1, 2021)
A catastrophic failure occurred on the carbon steel piping system of a steam generator after 20 years of operation. The failure occurred at a time when the system experienced a slight increase in pressure of approximately 300 psig more than its normal operating pressure, but 775 psig below the design pressure. Three failed sections at welded joints of the 2” and 3” Ø piping indicated different failure modes and suggested erosion-corrosion, material deterioration and weld imperfections all contributed to the cause of failure. Based on the analysis conducted it was also suggested that the failure involved more than one failure mechanism it included one that initiated the failure and another that eventually destroyed the parts. The long-term deterioration of the 2?Ø elbow showed the Longitudinal cracks that developed due to hoop stress allowed steam to escape into the atmosphere, then at ‘down times’ moisture from the environment penetrated the crack and assisted in the corrosion process. The weld imperfections of the 3” Ø pipeline which was also compromised by the corrosion process could not withstand the increase pressure and failed in a transverse manner thus allowing the other joints to fail in a similar manner. Methods to mitigate similar failures are discussed in terms of following established welding procedures and adopting preventative maintenance procedures.